Study of pre-conception care (PCC) amongst women in the first trimester coming to the obstetrics and gynaecology (OBGY) outpatient department (OPD) of a hospital in a rural area - Rucha D. Phalke; Riddhi T. Patil; Pawni Jain; Pratikesh S. Patil; Harshada G. Ambekar; Vaishali D. Phalke (Journal of Family Medicine and Primary Care)
Background: Pre-conception care (PCC) is a set of interventions that aim to identify and modify biomedical, behavioural and social risks to women’s health and pregnancy outcomes. Materials and Methods: It was an observational descriptive cross-sectional study conducted in the obstetrics and gynaecology (OBGY) outpatient department (OPD) of a tertiary care teaching institute in a rural set-up. Two hundred women in the first trimester of pregnancy were interviewed using a pre-designed and pretested questionnaire following informed verbal consent. The study was conducted between May and September 2019. The study excluded women in the 2nd or 3rd trimester of pregnancy, inpatient department (IPD) patients and those unwilling to participate. Results: The study revealed that 25.5% of the women had conceived between 14 and 19 years of age. Fifty-four percent of the pregnancies were unplanned. Merely 14.5% had consulted and 15% had their laboratory investigations performed before pregnancy. Only 11% had received pre-conception folic acid supplementation. Pregnancies with birth spacing <2 years accounted for 15%. The proportion of women with known risk factors was 38% being underweight, 9.5% being overweight, 8% being of short stature (height ≤145 cm), 63% having anaemia (haemoglobin <12 g/dL), 10% with a previous history of abortion, 3.5% with systemic diseases, 4.5% with poor oral hygiene, 1% with domestic violence, 3% with medication, 3% with tobacco addiction and 4.5% with radiation/environmental toxin exposure. One percent had the hepatitis B vaccine and 0.5% had the influenza vaccine. Conclusion: From our study, we conclude that the PCC services are meagre, and unhealthy women who conceive without adequate PCC are prone to maternal and foetal health complications.